Family Empowerment Model for Type 2 DM Management: Integration of Self care Model by Orem and Family Centered Nursing by Friedman in Sikumana Health Center-Kupang - Margaretha Teli (JURNAL INFO KESEHATAN, 2019)
Background. The management of Diabetes which is very complex needs full support from the family. The family has a vital role in management type 2 diabetes at home involving diabetes diet, diabetes medication management, exercise, and also visit health care services for checking blood glucose and diabetes discussion session. Unfortunately, the family is rarely Involved in the health education session. The research aimed to identify the effect of family empowerment models: Integrated self-care model by Orem and Family-Centered Nursing by Friedman in type 2 DM management in Sikumana Health Center of Kupang. Methods. The research design was pra-experimental design with "One Group Pretest - Posttest approach. The population of this study was 30 family members with type 2 DM. The data was collected by using questionnaires to measure the family members' ability to know type 2 DM, to make a proper decision, to take care of family members in term of diabetes diet management and to use health care services. Wilcoxon signed-Rank Test is used to figure out the effect of family empowerment model to conduct five family health function. Results. The study showed that the model improved the five health function performance by family members. While Wilcoxon signed-rank test also showed there was a significant effect of family empowerment model in terms of the family's ability to recognize type 2 DM (p =0.0001), to make a right decision to take care the patient (p = 0.0005). Moreover, the models have also improved the family ability to diabetes diet management (p=0,046), to motivate the patient to do regular exercise and to uses the health care facilities (p=0,014 and 0,025 respectively). Conclusions. The study recommended to actively involve the family members to take care of type 2 diabetes patient due to it affects the entire family. The family members should be well informed so that they can improve the quality of family health.